The role of periodontitis in the link between alpha-tocopherol intake and cognitive performance: A mediation analysis in older adults - Zhang, Heming; Sun, Li; Zhang, Lin; Li, Jiangjing; Liu, Yongfei; Chen, Zhiyang; Wang, Shuang; Gao, Changjun; Sun, Xude (Frontiers in Aging Neuroscience, 2023)
Background Epidemiological evidence on alpha (α)-tocopherol intake and cognitive performance in older individuals is controversial and the effect of periodontitis in this chain is sparse and limited. The goal of this study was to characterize the association between α-tocopherol intake and cognitive performance and the mediating role of periodontitis in a nationally representative sample of older adults. Methods Data from the National Health and Nutrition Examination Survey (NHANES), 2011–2014, were used. Multivariate logistic regression analysis was performed to explore the association of α-tocopherol intake, periodontal measures (mean attachment loss [AL] and mean probing depth [PD]), and clinical periodontitis defined by the European Workshop in Periodontology with poor cognitive performance evaluated by Consortium to Establish a Registry for Alzheimer’s disease (CERAD); the animal fluency test (AFT); and the Digit Symbol Substitution test (DSST) and the correlation between α-tocopherol intake and clinical periodontitis. Multiple linear regression analysis was used to explore the relationship between α-tocopherol intake and periodontal measures. Mediation analysis was used to test the effects of periodontal measures on the association between α-tocopherol intake and cognitive measures. Results A total of 1,749 older participants (≥60 years of age) with complete periodontal diagnosis, dietary retrospective survey, and cognitive tests were included. In the fully adjusted model, the odds ratio (OR) with 95% confidence interval (CI) of CERAD score, AFT score and DSST score were 0.214 (0.137–0.327), 0.378 (0.241–0.585) and 0.298 (0.169–0.512) for the highest versus lowest tertile of α-tocopherol intake, respectively. And participants with clinical periodontitis were more likely to exhibit lower DSST score (OR = 1.689; 95 CI%: 1.018–2.771) than those without periodontitis. Mean AL (OR = 1.296; 95 CI%: 1.102–1.524) and PD (OR = 1.667; 95 CI%: 1.18–2.363) were negatively correlated with DSST, and were estimated to mediate 9.1 and 8.2% of the total association between α-tocopherol intake and cognitive performance, respectively. Conclusion Finding of the present study suggested that participants with low α-tocopherol intake were at higher risk for developing cognitive decline. Moreover, periodontitis mediated the association between α-tocopherol intake and cognitive performance.